Methods and background characteristics of the TOHNN study: a population-based study of oral health conditions in northern Norway - Holde, Gro Eirin; Oscarson, Nils; Tillberg, Anders; Marstrander, Peter; Jönsson, Birgitta (International Journal of Circumpolar Health, 2016)
This is an Open Access article distributed under the terms of the Creative Commons Attribution 4.0 International License , allowing third parties to copy and redistribute the material in any medium or format and to remix, transform, and build upon the material for any purpose, even commercially, provided the original work is properly cited and states its license. This article is also available via DOI: 10.3402/ijch.v75.30169 Objectives. The aim of the Tromstannen Oral Health in Northern Norway (TOHNN) study was to investigate oral health and dental-related diseases in an adult population. This article provides an overview of the background of the study and a description of the sample characteristics and methods employed in data collection. Study design. Cross-sectional population-based study including a questionnaire and clinical dental examination. Methods. A randomly selected sample of 2,909 individuals (2079 years old) drawn from the population register was invited to participate in the study. The data were collected between October 2013 and November 2014 in Troms County in northern Norway. The questionnaire focused on oral health-related behaviours and attitudes, oral health-related quality of life, sense of coherence, dental anxiety and symptoms from the temporomandibular joint. The dental examinations, including radiographs, were conducted by 11 dental teams in 5 dental offices. The examination comprised of registration of dental caries, full mouth periodontal status, temporomandibular disorders, mucosal lesions and height and weight. The participants were grouped by age (2034, 3549, 5064 and 6579) and ethnicity (Norwegian, Sa´mi, other European and other world). Results. From the original sample of 2,909 individuals, 1,986 (68.3%) people participated, of whom 1,019 (51.3%) were women. The highest attendance rate was among women 2034 years old (80.3%) and the lowest in the oldest age group of women (55.4%). There was no difference in response rate between rural and urban areas. There was a positive ...